Subclinical Left Ventricular Dysfunction Prevention in Breast Cancer Patients after FAC Chemotherapy: A Carvedilol Trial - Astuti, Astri; Sumantra, I Gede; Aafiyah, Adila; Abdurahman, R. Maman; Sihite, Teddy Arnold; Akbar, Mohammad Rizki; Hasan, Melawati; Martanto, Erwan (International Journal of Integrated Health Sciences, 2024)
Objective:  To assess the cardioprotective effects of Carvedilol in preventing subclinical left ventricular dysfunction (SLVD) in breast cancer patients after completing FAC chemotherapy.Methods: This prospective study employed a quasi-experimental clinical trial conducted from September 2018 to May 2019. Breast cancer patients receiving FAC chemotherapy were divided into two groups: intervention (IG) and control (CG). The IG received Carvedilol 6.25 mg b.i.d., which was increased every three weeks until reaching a tolerated dose. The study evaluated changes in left ventricular global longitudinal strain (GLS) and the incidence of SLVD (GLS reduction ≥15% and GLS >-18%) 24 weeks after initiating the FAC regimen.Result: Of the 81 women enrolled in the study, 31 were in the IG. No significant changes in GLS were observed during or after completing FAC chemotherapy in the IG, whereas the CG showed contradictory results. At the end of the follow-up period, the delta GLS reduction was lower in the IG (0.7; 95% CI -0.60, 3.60) compared to the CG (3.00; 95% CI -2.16, 4.19), with a p-value of 0.035. Similarly, the percentage reduction in GLS was 3.6% in the IG and 14.29% in the CG, resulting in a p-value of 0.05. The incidence rate of SLVD (GLS reduction ≥15% and GLS > -18%) was lower in the IG (41.9% and 25.8%) than in the CG (58% and 48%).Conclusion: Carvedilol may have a cardioprotective effect in preventing the incidence of SLVD, as evaluated by GLS reduction and changes, in women with breast cancer after completing a full cycle of the FAC regimen.